Maternal total energy, macronutrient and vitamin intakes during pregnancy associated with the offspring's birth size in the Japan Environment and Children's Study. Issue 6 (21st April 2020) - Eshak, Ehab S.; Okada, Chika; Baba, Sachiko; Kimura, Takashi; Ikehara, Satoyo; Sato, Takuyo; Shirai, Kokoro; Iso, Hiroyasu; ,
Abstract: Maternal diet during pregnancy can influence fetal growth; however, the available evidence is controversial. We aimed to assess whether maternal diet of Japanese women in mid-pregnancy can affect their offspring's birth size via collection of questionnaire and medical record data. The studied sample was a large cohort of paired mothers and their singleton offspring ( n 78 793) from fifteen areas all over Japan who participated in the Japan Environment and Children's Study. The mid-pregnancy intakes of total energy, macronutrients and vitamins were lower than the recommended intakes for pregnant Japanese women. Maternal total energy intake was positively associated with the offspring's birth weight; there was a 10-g mean difference in the offspring's birth weight of mothers in the lowest (3026 g) v . highest (3036 g) quartiles of energy intake. Carbohydrate intake was positively associated with the offspring's birth length (mean difference of 0·7 cm) and inversely associated with the ponderal index (mean difference of 0·8 g/cm 3 ). Offspring of mothers in the highest v . lowest quartiles of total dietary fibre intake were on average 9 g heavier and had 0·3 cm longer birth length and 0·2 cm longer head circumference. The highest in reference to lowest intake quartile of vitamin C was associated with 13 g and 0·7 cm mean differences in the offspring's birth weight and length, respectively. Several other associations were evident for maternal intakes of vitamins and the offspring's birth size. In conclusion, maternal dietary intakes of energy, dietary fibre, carbohydrate and vitamins during pregnancy were associated with the offspring's birth size.